Virtual Reality Media for Introducing Gender Wayang Instruments Based on Tri Hita Karana - Ananta Wijaya, Gde Indra; Sukajaya, I Nyoman; Hendra Divayana, Dewa Gede (Jurnal Paedagogy, 2025)
This research aims to develop a virtual reality application for gender wayang that can enhance students’ understanding and appreciation of Balinese culture. Focusing on the challenges of preserving traditional Balinese art in the digital era, this study uses virtual reality technology to create a more interactive and enjoyable learning experience. The Research and Development (R&D) method with the ADDIE model was employed, combining quantitative and qualitative approaches for data analysis. The study was conducted at Dewi Ratih Batu Bulan Art Studio, where 20 students participated in trying the application and filling out questionnaires. The results showed that the developed virtual reality gender wayang application obtained a very high level of validity, with an average Aiken’s V of 0.900 from experts. Student responses indicated an average score of 2.98 on indicators of interest, loyalty, concern, and appreciation for local culture, demonstrating the application’s effectiveness in fostering students’ interest and concern for gender wayang and Balinese culture preservation. This research highlights virtual reality’s potential to enrich students’ learning experiences and strengthen their connection to cultural heritage.